The holy spirit and lay ecclesial ministry: Reflections for the 2020 plenary council - Trinidad, Julie (The Australasian Catholic record, 2019)
In this article, I argue that the growing phenomenon of lay ecclesial ministry is a hope-filled work of the Spirit leading the church into deeper reception of conciliar renewal. The upcoming plenary council's consideration of future directions for the church in Australia will have implications for the development of ecclesial ministry models. The experience of lay ecclesial ministry points to the future of how emerging models might look and function. In this article, I draw on the pneumatology of German theologian Walter Kasper. For Kasper, the Spirit brings about the new, opens up the future and makes space for the flourishing of life. Kasper's theology of the Spirit can be illustrated in the changing face of ministry since Vatican II. In the light of this I propose a number of implications for deeper reception of lay ecclesial ministry in and for the life and mission of the Catholic Church in Australia.